2019
DOI: 10.3329/jom.v21i1.44109
|View full text |Cite
|
Sign up to set email alerts
|

Changing trend of antibiotic susceptibility pattern of Enteric Fever: What is Next?

Abstract: Enteric fever continues to be a major global public health problem, predominantly in the developing countries, including Bangladesh. Mortality rates due to enteric fever can be reduced from 30% to <1% by providing effective antimicrobial therapy which is facing challenges due to emerging antimicrobial resistance. The changing trend of antibiotic susceptibility pattern of Enteric fever from pre-antibiotic era through susceptible antibiotics, then multidrug resistance (MDREF) followed by re-emergence of sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Also, Islam et al [34] reported in a study conducted in Bangladesh that only 28 (32.5%) out of 86 S. typhi isolates showed resistance to chloramphenicol, suggesting more susceptibility than resistance. Similarly, in a review of 6 different studies conducted in different countries of the world including Bangladesh, Ahasan et al [35] reported increasing susceptibility of salmonella isolates to the first line antibiotics chloramphenicol, ampicillin and cotrimoxazole. Ayalu et al [8] and Baya et al [10] however, reported resistance to chloramphenicol in their findings.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Also, Islam et al [34] reported in a study conducted in Bangladesh that only 28 (32.5%) out of 86 S. typhi isolates showed resistance to chloramphenicol, suggesting more susceptibility than resistance. Similarly, in a review of 6 different studies conducted in different countries of the world including Bangladesh, Ahasan et al [35] reported increasing susceptibility of salmonella isolates to the first line antibiotics chloramphenicol, ampicillin and cotrimoxazole. Ayalu et al [8] and Baya et al [10] however, reported resistance to chloramphenicol in their findings.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings revealed that chloramphenicol is currently not commonly prescribed in the study area. Suspending the use of an antibiotic to which resistance has developed over a period, could reverse the trend, and restore its effectiveness by the elimination of selective pressure [1,35]. Also, the increase in susceptibility of S. typhi to chloramphenicol as observed in this study could have resulted from the emergence of new susceptible strains and the loss of selftransmissible, high molecular weight plasmids by the bacterium [36].…”
Section: Discussionmentioning
confidence: 99%